Rambu Pembatas Dan Perluasan Kewenangan Mahkamah Konstitusi - Moh. Mahfud MD (Fakultas Hukum Universitas Islam Indonesia, 2009)
Generally, public society acknowledgment of the productivity & achievement of Constitutional Court are known since its born, but in the other side, it seems need border & guardrail in the authority realization of Constitutional Court in order to bounded the authority that given by UUD 1945. Realizing in developmental of Indonesian Constitutional law, there?s some issues which needs to be patched in authority range of Constitutional Court such as Constitutional Complaint and Constitutional.Key words : border sign, expanded authority, constitutional kourt